2013
DOI: 10.1186/1750-1172-8-122
|View full text |Cite
|
Sign up to set email alerts
|

Screening for duplications, deletions and a common intronic mutation detects 35% of second mutations in patients with USH2A monoallelic mutations on Sanger sequencing

Abstract: BackgroundUsher Syndrome is the leading cause of inherited deaf-blindness. It is divided into three subtypes, of which the most common is Usher type 2, and the USH2A gene accounts for 75-80% of cases. Despite recent sequencing strategies, in our cohort a significant proportion of individuals with Usher type 2 have just one heterozygous disease-causing mutation in USH2A, or no convincing disease-causing mutations across nine Usher genes. The purpose of this study was to improve the molecular diagnosis in these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
38
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 25 publications
2
38
0
Order By: Relevance
“…No duplications were identified. Steele et al 22 identified also USH2A deletions with similar frequency, as deletions were identified in 5% (7/121) unselected USH2 patients.…”
Section: Disussionmentioning
confidence: 84%
See 1 more Smart Citation
“…No duplications were identified. Steele et al 22 identified also USH2A deletions with similar frequency, as deletions were identified in 5% (7/121) unselected USH2 patients.…”
Section: Disussionmentioning
confidence: 84%
“…21,22 Investigation of PCDH15 revealed two deletions of 55 kb (exon 3 including the flanking introns) and 82 kb (exon 4-6 including the flanking introns), respectively, 21 whereas investigation of USH2A revealed one duplication (from exon 4 to exon 13) and five deletions (exon 4, exons 22-23, exon 27, exon 40 or exon 70 respectively). 22 Here we used MLPA to screen a cohort of 50 Danish USH patients (20 USH1 and 30 USH2) for exon deletions and duplications in PCDH15 and USH2A.…”
Section: Introductionmentioning
confidence: 99%
“…Braun and co-workers were first to provide evidence for the possibility of intronic variants near rare alternate splice junctions that could be pathogenic by increasing the probability of mis-splicing at these sites [65]. Deep intronic mutations leading to truncated proteins have also been described in Usher syndrome and LCA [66, 67]. This need to be further investigated in our 6 patients.…”
Section: Discussionmentioning
confidence: 96%
“…21,22 Moreover, several studies have demonstrated that copy number variants (CNVs) of some USH genes account for certain proportions of mutations. 23,24 Most of these CNVs are heterozygous and cannot be detected by Sanger sequencing or APEX. These kinds of genomic DNA rearrangements must be detected by other techniques, such as real-time quantitative polymerase chain reaction (q-PCR), multiplex ligation-dependent probe amplification (MLPA), or comparative genomic hybridization (a-CGH).…”
mentioning
confidence: 99%
“…These kinds of genomic DNA rearrangements must be detected by other techniques, such as real-time quantitative polymerase chain reaction (q-PCR), multiplex ligation-dependent probe amplification (MLPA), or comparative genomic hybridization (a-CGH). 23 Next-generation sequencing (NGS) technologies developed in recent years can perform whole genome; whole exome; and targeted exome sequencing (TES). 25 Several studies have proven TES as a highefficiency method of molecular diagnosis of USH, with a detection rate of around 70%.…”
mentioning
confidence: 99%